OHS Promotion About Use of Personal Protective Equipment for Pest Control Workers at CV. Pestex Indonesia - Dwi Anisafaul Latifaf; Ainur Rachman; Mardiana Mardiana; Yuliana Yuliana; Ramadhani Nur; Nurhafidah Kamila Mahmud; Abdul Farhan Al Badriansyah; Sheren Amalia Bodang; Amril Abdullah; Muhammad Said (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2023)
Pest control is a work that focuses on reducing and tackling various kinds of insects and pests that are disturbing or damaging to the surrounding environment, especially in the industrial or commercial sector. OSH is a science of occupational safety and health that must be applied in a company to reduce the risk of work accidents. The purpose of this activity was to protect worker safety so that workers are free from work accidents and health problems. This activity used the observation method. The sample in this Field Work Practice activity were 5 technicians. Before carrying out work, workers must observe the place to be visited for treatment such as fogging or cold fogging. From the activities carried out, the response of the workers was very good, as evidenced when providing material related to the dangers of inhaling fogging smoke, the workers listened carefully, and also the workers began to take care of the work environment by disposing of garbage in its place and complying with the use of PPE when doing work. The conclusion from the activities that have been carried out, it can be concluded that workers are starting to understand how to work safety.